The Packaging Regions of G1-Like PB2 Gene Contribute to Improving the Survival Advantage of Genotype S H9N2 Virus in China - Li, Xiuli; Zhao, Ying; Qiao, Shumiao; Gu, Min; Gao, Ruyi; Ge, Zhichuang; Xu, Xiulong; Wang, Xiaoquan; Ma, Jing; Hu, Jiao; Hu, Shunlin; Liu, Xiaowen; et al. (Frontiers in Microbiology, 2021)
The genotype S (G57) H9N2 virus, which first emerged in 2007 with the substitution of the G1-like PB2 gene for F98-like ones, has become the predominant genotype in the past 10 years. However, whether this substitution plays a role in the fitness of genotype S H9N2 viruses remains unknown. Comparison of the PB2 genes of the F98-like and G1-like viruses revealed a close homology in amino acid sequences but great variations at nucleotide levels. We then determined if the packaging region, a unique sequence in each segment utilized for the assembly of the vRNA into virions, played a role in the fitness of the S genotype. The chimeric H9N2 virus with PB2 segments of the G1-like packaging regions significantly increased viral protein levels and polymerase activity. Substituting the packaging regions in the two terminals of F98-like PB2 with the sequence of G1-like further improved its competitive advantage. Substitution of the packaging regions of F98-like PB2 with those of G1-like sequences increased the infectivity of the chimeric virus in the lungs and brains of chicken at 3 days post infection (dpi) and extended the lengths of virus shedding time. Our study suggests that the packaging regions of the G1-like PB2 gene contribute to the dominance of the genotype S H9N2 virus in China.